Elevated Mitochondrial Reactive Oxygen Species and Cellular Redox Imbalance in Human NADPH-Oxidase-Deficient Phagocytes - Sundqvist, Martina; Christenson, Karin; Björnsdottir, Halla; Osla, Veronica; Karlsson, Anna; Dahlgren, Claes; Speert, David P.; Fasth, Anders; Brown, Kelly L.; Bylund, Johan (Frontiers in Immunology, 2017)
Chronic granulomatous disease (CGD) is caused by mutations in genes that encode the NADPH-oxidase and result in a failure of phagocytic cells to produce reactive oxygen species (ROS) via this enzyme system. Patients with CGD are highly susceptible to infections and often suffer from inflammatory disorders; the latter occurs in the absence of infection and correlates with the spontaneous production of inflammatory cytokines. This clinical feature suggests that NADPH-oxidase-derived ROS are not required for, or may even suppress, inflammatory processes. Experimental evidence however implies that ROS are in fact required for inflammatory cytokine production. By using a myeloid cell line devoid of phoxROS and primary CGD cells we analyzed intracellular oxidants, signs of oxidative stress and inflammatory cytokine production. Herein we demonstrate that phagocytes lacking a functional NADPH-oxidase, namely primary CGD phagocytes and a gp91phox-deficient cell line, display elevated levels of ROS derived from mitochondria. Accordingly these cells, despite lacking the major source of cellular ROS, display clear signs of oxidative stress, including an induced expression of antioxidants and altered oxidation of cell surface thiols. These observed changes in redox state were not due to abnormalities in mitochondrial mass or membrane integrity. Finally we demonstrate that increased mitochondrial ROS enhanced phosphorylation of ERK1/2, and induced production of IL8, findings that correlates with previous observations of increased MAPK activation and inflammatory cytokine production in CGD cells. Our data show that elevated baseline levels of mitochondria-derived oxidants lead to the counter-intuitive observation that CGD phagocytes are under oxidative stress and have enhanced MAPK signalling, which may contribute to the elevated basal production of inflammatory cytokines and the sterile inflammatory manifestations in CGD.